Factitious hyperamylasuria by a nurse: symptom of Munchausen's syndrome. Issue 1 (20th December 2006) - Nasser, N J; Israelit, S H; Muhammad, M; Basis, F
Abstract : A 30-year-old nurse presented with abdominal pain and tenderness. Her blood tests, including amylase, were normal. Urinary amylase was extremely high. The source of the increased urinary amylase was found to be the patient's saliva — she had spit into her urine sample. Subsequent investigation showed that she had Munchausen's syndrome.